La cartographie sensible et participative comme levier d’apprentissage de la géographie - Sophie Gaujal (VertigO)
This article presents a sensitive et participatory mapping experience with high school french student about their own school establishment. The purpose was the hybridization of various knowledges in the class (formal and informal, individual and collective), where the usual practices are focused on formal knowledge only.